Living Together in a Tolerant Society: Non-Muslim Armenian Citizens and Law in the Ottoman Society: A Case Study of Kayseri - Süleyman DEMİRCİ (Fırat University, 2019)
Tolerance occupying an important place in our cultural and civilized life is often described as overlooking the faults, respecting different ideas and cultures, and forgiving everything that is forgivable. However, nobody should have the right to act tolerantly on behalf of tolerance under the conditions where the law of others are in the foreground. As in